Individual and synergistic effects of modifications of the carrier medium of carbon-containing slurries on the viscosity and sedimentation stability; Chemical Engineering Research and Design; Vol. 184 - Piskunov M. V. Maksim Vladimirovich; Romanov D. S. Daniil Sergeevich; Strizhak P. A. Pavel Alexandrovich; Yanovsky V. A. Vyacheslav Aleksadrovich (2022, 2022)
Title screen